Demographic and Geographic Distribution of Pancreatic Cancer: A Five‑Year Retrospective Study at the National Institute of Oncology, Sabratha - Gueder, Nahla; Nadya Alwaer,; Azab Elsayed Azab,; Muhanad Alqazoun,; Mohammed Waydran, (AlQalam Journal of Medical and Applied Sciences, 2026)
Pancreatic cancer is recognized as a highly aggressive disease with a poor overall outlook. Although its occurrence differs across regions, information from Libya and several surrounding countries remains limited. This study describes the demographic characteristics and geographic distribution of patients diagnosed with pancreatic cancer at a major oncology center in Western Libya, aiming to support local health planning. A 5-year retrospective study (2020–2024) was conducted at the National Institute of Oncology-Sabratha. The files of patients with radiological and/or histopathological confirmation of pancreatic cancer were reviewed. Demographic variables and place of residence were evaluated, and basic statistical tests, including chi-square and Fisher’s exact tests, were applied. Of the 91 included patients, 52 (57.14%) were male, and 39 (42.86%) were female. The majority of cases occurred in individuals aged 50–69 years. Female patients tended to present at a younger age, though this was not statistically significant. Most patients were from coastal areas, particularly Zawia (25.3%) and Tripoli (19.8%). No significant associations were found between sex and year of admission, age group, or region of origin. This study demonstrates a slight male predominance in pancreatic cancer incidence in Western Libya, aligning with global trends, with a descriptive geographical clustering in industrialized coastal areas. The findings underscore the need for enhanced cancer registry data and targeted public health initiatives. Future research with larger cohorts is recommended to investigate potential environmental, occupational, and lifestyle risk factors contributing to these observed patterns.